Low/No calorie sweetened beverage consumption in the National Weight Control Registry. (10th July 2014) - Catenacci, Victoria A.; Pan, Zhaoxing; Thomas, J. Graham; Ogden, Lorraine G.; Roberts, Susan A.; Wyatt, Holly R.; Wing, Rena R.; Hill, James O.
<x xml:space="preserve">Abstract</x> Objective The aim of this cross‐sectional study was to evaluate prevalence of and strategies behind low/no calorie sweetened beverage (LNCSB) consumption in successful weight loss maintainers. Methods An online survey was administered to 434 members of the National Weight Control Registry (NWCR, individuals who have lost ≥13.6 kg and maintained weight loss for > 1 year). Results While few participants (10%) consume sugar‐sweetened beverages on a regular basis, 53% regularly consume LNCSB. The top five reasons for choosing LNCSB were for taste (54%), to satisfy thirst (40%), part of routine (27%), to reduce calories (22%) and to go with meals (21%). The majority who consume LNCSB (78%) felt they helped control total calorie intake. Many participants considered changing patterns of beverage consumption to be very important in weight loss (42%) and maintenance (40%). Increasing water was by far the most common strategy, followed by reducing regular calorie beverages. Conclusions Regular consumption of LNCSB is common in successful weight loss maintainers for various reasons including helping individuals to limit total energy intake. Changing beverage consumption patterns was felt to be very important for weight loss and maintenance by a substantial percentage of successful weight loss maintainers in the NWCR.